High dynamic extinction ratio and pulse modulation of optical signals. (October 2015) - Petrov, A; Tronev, A V; Lebedev, V; Il'ichev, I V; Velichko, E; Shamray, A
Abstract: The use of a saturable absorber for increasing the extinction ratio at external modulation of optical signals is considered. An erbium doped fiber was used as the saturable absorber in the experiments. A considerable increase in the static extinction ratio (up to 50 dB) was demonstrated. A rather long erbium doped fiber relaxation time (about 10 ms) was a limiting factor in the case of pulse modulation. Ways of overcoming this drawback are discussed.